2019
DOI: 10.2174/1874350101912010020
|View full text |Cite
|
Sign up to set email alerts
|

The Working Environment as a Platform for the Promotion of Active Aging: An Italian Overview

Abstract: European data confirm a gradual and constant aging of the population. The reduction of risk factors for chronic diseases and the improvement of health care have increased life expectancy in general. In January 2018, Italy recorded a mean age of 45.2 years (two tenths more than 2017). "The 2018 Ageing Report", an economic paper of the European Community, predicts that the European Union would go from having 3.3 working-age people for every person aged over 65 years to only two working-age persons. If this happe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…In Italy, a survey by the National Institute for Insurance Against Workplace Injuries (INAIL), as early as 2014, [ 45 ] revealed a deterioration in the perception of individual health status directly related to age, with the share of workers declaring very good health status varying from 49% among the workers between 16 and 24 years of age to 14% among those aged between 55 and 64, with a close correspondence between age and the trend of accidents at work. An appropriate active-aging program could provide a motivational stimulation among older workers, resulting in an improvement in workers’ psychophysical wellbeing and consequent reductions in absenteeism, accidents, and limitations at work [ 46 , 47 ]. The offering of health screenings to monitor the health of workers and encourage healthy workplace habits and good practices and promote active living, healthy eating, stress management, and work-life balance initiatives is expected to play a role in maintaining the health and safety of aging workers [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, a survey by the National Institute for Insurance Against Workplace Injuries (INAIL), as early as 2014, [ 45 ] revealed a deterioration in the perception of individual health status directly related to age, with the share of workers declaring very good health status varying from 49% among the workers between 16 and 24 years of age to 14% among those aged between 55 and 64, with a close correspondence between age and the trend of accidents at work. An appropriate active-aging program could provide a motivational stimulation among older workers, resulting in an improvement in workers’ psychophysical wellbeing and consequent reductions in absenteeism, accidents, and limitations at work [ 46 , 47 ]. The offering of health screenings to monitor the health of workers and encourage healthy workplace habits and good practices and promote active living, healthy eating, stress management, and work-life balance initiatives is expected to play a role in maintaining the health and safety of aging workers [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It means that more than half leave work before achieving retirement age. Mucci [37] emphasizes that this trend is destructive for European economies, and, therefore, it is necessary to extend the professional life of elderly people through active aging technologies. The working environment is an ideal platform for promoting active aging, for supporting the psychophysical abilities of employees and preserving their ability to work, and for developing cooperation between generations.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing age of the workforce presents opportunities and challenges for governments, employers and health professionals, but also for individual employees and their families. In a recent overview of European legislation and research concerning older workers, it was concluded that the working environment is an ideal platform to carry out initiatives to promote active and healthy ageing (Mucci et al 2019). It is now essential to facilitate sustainable working and extend working lives by promoting health in the workplace.…”
Section: Introductionmentioning
confidence: 99%